Peran Ustaz Menanamkan Nilai-nilai Religius di Pondok Pesantren Tarbiyatul Athfal Kuningan Jawa Barat - Arrizqi Fiddinillah; Ahmad Syathori; Darrotul Jannah (At-Tarbawi: Jurnal Kajian Kependidikan Islam, 2021)
Ustaz is the most influential person in the process and quality of educational outcomes. Therefore, the role ofustaz is needed as someone who is able toinstilreligious values forstudents. One of the efforts of Tarbiyatul Athfal Islamic Boarding School by holding religious activities so that there is no moral decline. This study aims to determine the rolesof ustaz in instilling religious values, some religiousstudents activitiesthat are able to increase the religious value of students and teacher obstacles in instilling religious values. The researchuseddescriptive qualitativemethod. Data collection techniques usedparticipatory observation, in-depth interviews, documentation. The data analysis technique utilizeddata reduction, data presentation, and conclusion drawing. The research showed that the role of the ustaz in instilling religious values through religious activities in students at the Tarbiyatul Athfal Islamic Boarding School is giving love to students like their own children, setting a good example, paying attention, advising, protecting their students, not expecting remuneration, and directing the students study solely because of Allah SWT with religious values that are instilled in students through religious activities, namely the value of worship, the spirit of jihad, morals, exemplary, sincerity.